Riotous deathscapes - Canham, Hugo (Duke University Press, 2023)
"In Riotous Deathscapes, Hugo Canham presents an understanding of life and death based on indigenous and black ways of knowing that he terms Mpondo theory. Focusing on amaMpondo people from rural Mpondoland, in South Africa's Eastern Cape, Canham outlines the methodologies that have enabled the community's resilience and survival. He assembles historical events and a cast of ancestral and living characters, following the tenor of village life to offer a portrait of how Mpondo people live and die in the face of centuries of abandonment, trauma, antiblackness, and death. Canham shows that Mpondo theory is grounded in and develops in relation to the natural world, where the river and hill are key sites of being and resistance. Central too, is the interface between ancestors and the living, in which life and death become a continuity and a boundlessness that white supremacy and neoliberalism cannot interdict. By charting a course of black life in Mpondoland, Canham tells a story of blackness on the African continent and beyond. Duke University Press Scholars of Color First Book Award Recipient."--